IMPLEMENTATION OF THE NATIONAL MENTAL REVOLUTION MOVEMENT IN SUB-DISTRICT CARITA, PANDEGLANG REGENCY, BANTEN PROVINCE - Ajat Sudrajat; Ojat Darojat; Sofjan Aripin; Syaeful Mikdar; Heriyanto Heriyanto; Faizal Maulana; Ahmad Septianto (JURNAL SOCIUS, 2021)
There is still a lack of knowledge on the society in Carita District, Pandeglang Regency, Banten Province about the importance of character values. It happens because that is a remote area so that they rarely get direction and guidance, especially related to the value of the character, the solution is the need for a workshop about Implementation of the National Movement of the Revolutionary Mental in Sub-district Carita, Pandeglang Regency, Banten Province. The GNRM workshop is a movement to change the way of thinking of society or youth, change the way of work that has been done so far to be more advanced, change the way of life, as well as attitudes and behavior of society which will further improve aspects of integrity, high ethical aspects and the spirit of mutual cooperation based on Pancasila and the 1945 Constitution. This workshop is divided into two themes, namely: a) "Implementation of the Cultivation of National Character Values that support the National Movement of the Mental Revolution in the society of Carita Sub-district, Pandeglang Regency, Banten Province". The purpose of the workshop is of course very useful for the society in Carita Sub-district to understand the nature of the implementation of character values which will later be practiced in everyday life. b) "Local wisdom that supports the National Movement of Mental Revolution in the society of Carita Sub-district, Pandeglang Regency, Banten Province". The purpose of this workshop is that the society of Carita are expected to preserve local culture as a national cultural heritage that is not lost even with the very rapid development of the era and towards the era of society 4.0.